Research on Chemically Deuterated Cellulose Macroperformance and Fast Identification - Song, Yan; Liu, Shaoyang; Ben, Haoxi; Zhang, Yuanming; Han, Guangting; Ragauskas, Arthur J.; Jiang, Wei (Frontiers in Plant Science, 2021)
Chemically deuterated cellulose fiber was expected to provide novel applications due to its spectral, biological, and kinetic isotope effect. In this research, the chemically deuterated cotton fibers’ performance including mechanical property, enzymatic degradation performance, effect on bacterial treatment and fast identification (near-infrared modeling) were investigated. The breaking tenacity of the deuterated cotton fibers were slightly lower, which might be attributed to the structure damage during the chemical deuteration. The glucose yield by enzymatic hydrolysis were less than that of the protonic cotton fibers, meaning the deuterated fibers are less sensitive to enzymatic degradation. Furthermore, the deuterated fibers could promote the growth of bacterial such as E’coli, which was associated with the released low-level deuterium content. At last, the near-infrared technique combined with partial least squares regression successfully achieved a fast identification of the protiated and deuterated cotton fibers, which significantly promoted the potential application of deuterated cellulose as anti-counterfeiting materials (e.g., special paper).